Dating of fractures: an analysis of key radiological features in children aged 5 years and under. (29th September 2015) - Prosser, I; Maguire, S; Harrison, S; Evans, A; Morris, S; Lawson, Z; Kemp, A
Abstract : Aims: Given the clinical and legal significance of radiological fracture dating in child abuse, and the lack of primary data to support such estimations, the authors set out to determine the key radiological variables in fracture healing and their timeline. Methods: The authors analysed digital x-rays (initial and follow-up) of children 5 years of age and under, presenting to a single emergency department during 2008, with accidental fractures of known timing. The authors excluded children who had metabolic bone disease or non-accidental injury. X-rays were reviewed independently by three paediatric radiologists who were blinded to clinical details. They analysed the fractures for the presence or absence of six features of fracture healing: soft tissue swelling (STS), periosteal reaction, soft and hard callus, bridging and remodelling. Results: 213 of 78 fractures from 63 children (mean age 3.9 years) were analysed. The presence of casts in 114 cases limited interpretation. However, when STS was present, 88% of fractures were less than 2 days old; when periosteal reaction and soft callus were present, 59% and 89% of fractures were between 15 and 35 days, respectively; when hard callus and bridging were present, 96% were aged more than 22 days old; and remodelling was only found in fractures more than 36 days old. Further analysis of children under 1 year is ongoing. Conclusion: This large data set of young children defines the key features from which fracture dating can be estimated. It is possible to determine the age of a fracture as acute (less than 1 week), recent (2–5 weeks) and old (6 weeks or more) based on the presence or absence of six variables in combination. The application of this dating tool now needs to be validated in practise.